Pengaruh kualitas kerja dan pengawasan terhadap produktivitas kerja karyawan bank kaltimtara syariah cabang samarinda - Fahmi Indra Rosadi; Zainal Ilmi; Saida Zainurossalamia ZA (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
The purpose of this research is to know the influence of the quality of work and supervision conducted by the Samarinda Branch of Bank Kaltimtara Syariah on employee work productivity. This study involved 43 respondents whose results were tested using multiple regression analysis and t test.The results showed that the quality of work has a value of t greater than table t with a significance level of 0.008 while supervision shows a value of t smaller than table t with a significance level of 0.223. From the results of the analysis it can be concluded that the quality of work has a significant effect on the work productivity of sharia Kaltimtara bank employees, so the first hypothesis is accepted.While supervision does not affect the work productivity of sharia bank Kaltimtara employees, so the second hypothesis is rejected.